Ewolucja egzaminu maturalnego z języków obcych na przestrzeni sześciu dekad - Sendur, Agnieszka M. (Neofilolog, 2023)
Matura is an important high-stakes examination present in the Polish education system since the late 18th century. It is taken on completion of high school and is compulsory for those who want to apply for higher education. As a result of an examination reform, in 2005 the exam took on a new form. Since then it has been a professional, external, standardised assessment used for the analysis of school and student performance, and – most importantly – in lieu of university entrance exams. The article looks at the evolution of the foreign language component of the Matura exam over the last six decades: from an internal test prepared by local authorities and by schools, assessed arbitrarily by the test-takers’ teachers, to a professional examination prepared by expert institutions in compliance with quality standards and assessed by trained markers according to elaborate grading criteria. The paper follows the changes occurring in the assessment starting from 1960 up to 2023, when another examination reform brought about new modifications in the foreign language exam.